The sulfur-related metabolic status of Aspergillus fumigatus during infection reveals cytosolic serine hydroxymethyltransferase as a promising antifungal target - Reem Alharthi; Monica Sueiro-Olivares; Isabelle Storer; Hajer Bin Shuraym; Jennifer Scott; Reem Al-Shidhani; Rachael Fortune-Grant; Elaine Bignell; Lydia Tabernero; Michael Bromley; Can Zhao; Jorge Amich (Virulence)
Sulfur metabolism is an essential aspect of fungal physiology and pathogenicity. Fungal sulfur metabolism comprises anabolic and catabolic routes that are not well conserved in mammals, therefore is considered a promising source of prospective novel antifungal targets. To gain insight into Aspergillus fumigatus sulfur-related metabolism during infection, we used a NanoString custom nCounter-TagSet and compared the expression of 68 key metabolic genes in different murine models of invasive pulmonary aspergillosis, at 3 time-points, and under a variety of in vitro conditions. We identified a set of 15 genes that were consistently expressed at higher levels in vivo than in vitro, suggesting that they may be particularly relevant for intrapulmonary growth and thus constitute promising drug targets. Indeed, the role of 5 of the 15 genes has previously been empirically validated, supporting the likelihood that the remaining candidates are relevant. In addition, the analysis of gene expression dynamics at early (16 h), mid (24 h), and late (72 h) time-points uncovered potential disease initiation and progression factors. We further characterized one of the identified genes, encoding the cytosolic serine hydroxymethyltransferase ShmB, and demonstrated that it is an essential gene of A. fumigatus, also required for virulence in a murine model of established pulmonary infection. We further showed that the structure of the ligand-binding pocket of the fungal enzyme differs significantly from its human counterpart, suggesting that specific inhibitors can be designed. Therefore, in vivo transcriptomics is a powerful tool for identifying genes crucial for fungal pathogenicity that may encode promising antifungal target candidates.